Sustainable Urban Transportation Systems – Introduction (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
The chapter "Sustainable Urban Transportation Systems – Introduction" outlines the context of the research conducted by the respective authors in the subsequent parts of the book. Contemporary urban transport policy aims to shape sustainable, intelligent, and resilient transportation systems. Simultaneously, the ubiquitous dominance of personal vehicles as a means of mobility leads to numerous negative consequences such as traffic congestion and air pollution. Municipal authorities must confront these consequences while satisfying the needs of city users in terms of accessibility, reliability, and transportation safety. The main goal of the book is to diagnose the challenges facing modern urban transport policy, identify how transport users perceive these challenges, and explore the corresponding solutions implemented within urban transportation systems. The book consists of 7 chapters, each analyzing the following issues sequentially: traffic congestion; the quality of local public transportation services; determinants of using commuter rail; integration of rail and bicycle transportation in urban areas; implementation of intelligent transportation systems in cities; shared mobility in urban transportation systems; and the development of electromobility. All chapters present the results of research conducted among users of urban transportation systems. This has enabled interesting conclusions to be drawn, ultimately making the book an engaging source of knowledge for local government practitioners, students, and researchers interested in the issues of sustainable urban logistics.